Biopsychosocial Determinants of Early Marriage in Wonogiri District, Central Java: A Logistic Regression - Meylsa Rima Kamilda; Ismi Dwi Astuti Nurhaeni; Rita Benya Adriani (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2019)
Background: Early marriage is one of the problems in Indonesia and the developing countries. It represents one of the violations of women's human right. Early marriage had physical, psychological, and social negative effects in the affected women. This study aimed to examine the determinants of early marriage in Wonogiri District, Central Java.Subjects and Method: This was a case control study carried out in Wonogiri, Central Java, from October to November 2018. A sample of 200 women was selected by fixed disease sampling, consisting of 50 women with early marriage and 150 women with timely marriage. The dependent variable was early marriage. The independent variables were menarche age, unwanted pregnancy, education level, gender inequality, parental perception on early marriage, local culture, residence, and employment before marriage. The data were collected using questionnaires and analyzed by logistic regression.Results: The risk of early marriage increased with age of menarche <12 years (OR= 3.41; 95% CI= 1.12 to 10.36; p= 0.003), gender inequality (OR= 4.70; 95% CI= 1.53 to 14.40; p= 0.007), and local culture pro early marriage (OR= 5.33; 95% CI= 1.62 to 17.42; p= 0.006). The risk of early marriage decreased with wanted pregnancy (OR= 0.17; 95% CI= 0.043 to 0.70; p= 0.014), education level (OR= 0.03; 95% CI= 0.01 to 0.14; p= 0.001), positive parental perception (OR= 0.24; 95% CI= 0.08 to 0.77; p = 0.016), neighborhood in city (OR= 0.29; 95% CI= 0.09 to 0.93; p = 0.035), and work before marriage (OR= 0.20; 95% CI= 0.63 to 0.65; p = 0.007).Conclusion: The risk of early marriage increases with age of menarche <12 years, gender inequality, and local culture pro early marriage. It decreases with wanted pregnancy, education level, positive parental perception, neighborhood in city, and work before marriage.Keywords: early marriage, gender inequality, local cultureCorrespondence: